Comparison of bladder carcinogenesis biomarkers in the urine of traditional cigarette users and e-cigarette users - Lida Feng; Lida Feng; Lida Feng; Guixiao Huang; Lei Peng; Lei Peng; Rui Liang; Rui Liang; Dashi Deng; Shaohua Zhang; Guangzhi Li; Song Wu; et al. (Frontiers Media S.A., 2024)
BackgroundDuring the use of electronic cigarettes (e-cigarettes), users are still exposed to carcinogens similar to those found in tobacco products. Since these carcinogens are metabolized and excreted in urine, they may have carcinogenic effects on the bladder urinary tract epithelium. This meta-analysis aimed to compare bladder cancer carcinogens in the urine of tobacco users and e-cigarette users using a large number of samples.MethodsA systematic meta-analysis was performed using data obtained from several scientific databases (up to November 2023). This cumulative analysis was performed following the Preferred Reporting Items for Systematic Evaluation and Meta-Analysis (PRISMA) and Assessing the Methodological Quality of Systematic Evaluations (AMSTAR) guidelines, according to a protocol registered with PROSPERO. This study was registered on PROSPERO and obtained the unique number: CRD42023455600.ResultsThe analysis included 10 high-quality studies that considered polycyclic aromatic hydrocarbons (PAHs), volatile organic compounds (VOCs) and tobacco-specific nitrosamines (TSNAs). Statistical indicators show that there is a difference between the tobacco user group and the e-cigarette user group in terms of 1-Hydroxynaphthalene (1-NAP) [weighted mean difference (WMD)10.14, 95% confidence interval (CI) (8.41 to 11.88), p < 0.05], 1-Hydroxyphenanthrene (1-PHE) [WMD 0.08, 95% CI (−0.14 to 0.31), p > 0.05], 1-Hydroxypyrene (1-PYR) [WMD 0.16, 95% CI (0.12 to 0.20), p < 0.05], 2-Hydroxyfluorene (2-FLU) [WMD 0.69, 95% CI (0.58 to 0.80), p < 0.05], 2-Hydroxynaphthalene (2-NAP) [WMD 7.48, 95% CI (4.15 to 10.80), p < 0.05], 3-Hydroxyfluorene (3-FLU) [WMD 0.57, 95% CI (0.48 to 0.66), p < 0.05], 2-Carbamoylethylmercapturic acid (AAMA) [WMD 66.47, 95% CI (27.49 to 105.46), p < 0.05], 4-Hydroxy-2-buten-1-yl-mercapturic acid (MHBMA) [WMD 287.79, 95% CI (−54.47 to 630.04), p > 0.05], 4-(Methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNAL) [WMD 189.37, 95% CI (78.45 to 300.29), p < 0.05], or N0-nitrosonornicotine (NNN) [WMD 11.66, 95% CI (7.32 to 16.00), p < 0.05].ConclusionUrinary bladder cancer markers were significantly higher in traditional tobacco users than in e-cigarette users.Systematic review registration: PROSPERO (CRD42023455600: https://www.crd.york.ac.uk/PROSPERO/).